Voltammetric Studies of Gold, Protons, and [HCl2]- in Ionic Liquids - Aldous, L.; Silvester, Debbie; Pitner, W.; Compton, R.; Lagunas, M.; Hardacre, C. (American Chemical Society, 2007)
The comparative study of the voltammetry of H[NTf2], HCl and H[AuCl4] in [C4mim][NTf2] has provided an insight into the influence of protons on the reduction of [AuCl4]- at Au, Pt or glassy carbon (GC) electrodes, and has allowed the identification of an unprecedented proton-induced electroless deposition of Au on relatively inert GC surfaces. For the first time, clear evidence of the quantitative formation of [HCl2]- has been obtained in HCl/[C4mim][NTf2] mixtures, and the electrochemical behavior of these mixtures analyzed. In particular, a significant shift of the dissociation equilibrium toward the formation of chloride and the solvated proton (HIL+), following electrochemical reduction of HIL+ has been observed in the time-scale of the experiments.